Challenges in incorporating phase change materials into thermal control units for lithium-ion battery cooling. (May 2022) - Farouk, Naeim; Alotaibi, Abdullah Alhumaidi; Alshahri, Abdullah H.; Almitani, Khalid H.
Highlights: It was observed that the presence of PCM is not always advantageous. The presence of PCM can only be useful if the PCM undergoes phase changes. PCM effectiveness in thermal control unit (TCU) depends on convection coefficient (h). At h  = 5 W m 2 . K, the battery temperature dropped by 8 °C due to the PCM presence. At 20 W m 2 . K battery temperature was increased by 4.8 °C when PCM was loaded into TCU. Abstract: Keeping cool the lithium-ion battery improves its performance. In this study, focusing on battery cooling, a thermal control unit (TCU) containing metal fins was integrated into the battery. To boost TCU effectiveness, phase change material (PCM) was injected into it. By numerical solution, the temperature distribution in three areas of battery, fins and PCM was determined.  Using Fourier's law, TCU heat dissipation to the environment was evaluated at different convection coefficients (5, 10, and 20 W m 2 . K ). It was observed that the presence of PCM is not always advantageous. The presence of PCM can only be useful if the PCM undergoes phase changes. This happened at 5 W m 2 . K, and at best conditions, the battery temperature dropped by 8°C due to the PCM presence. After the melting process, the PCM presence significantly augmented the battery temperature. At 20 W m 2 . K battery temperature was increased by 4.8 °C when PCM was loaded into TCU. Therefore, adding PCM to TCU with convection coefficient is not recommended. Increasing the number of fins declined the battery temperature. If the number of fins increases from three to five, the battery cooled by 1 to 1.7°C at convection coefficient range of 5–20 W m 2 . K